Estimating the Geoelectric Field and Electric Power Transmission Line Voltage During a Geomagnetic Storm in Alberta, Canada Using Measured Magnetotelluric Impedance Data: The Influence of Three‐Dimensional Electrical Structures in the Lithosphere - Darcy Cordell; Martyn J. Unsworth; Benjamin Lee; Cedar Hanneson; David K. Milling; Ian R. Mann (Space Weather)
Abstract Estimating the effect of geomagnetic disturbances on power grid infrastructure is an important problem since they can induce damaging currents in electric power transmission lines. In this study, an array of magnetotelluric (MT) impedance measurements in Alberta and southeastern British Columbia are used to estimate the geoelectric field resulting from a magnetic storm on September 8, 2017. The resulting geoelectric field is compared to the geoelectric field modeled using the more common method that uses a piecewise‐continuous 1‐D conductivity model. The 1‐D model assumes horizontal layers, which result in orthogonal induced electric fields while the measured MT impedance data can account for fully 3‐D conductivity structure. The geoelectric field derived from measured MT impedance data is partially polarized in southern Alberta, and the geoelectric field magnitude is largest in northeastern Alberta where the resistive Canadian Shield outcrops. The induced voltage in the Alberta transmission network is estimated to be ∼120 V larger in northeastern Alberta when using the measured MT impedances compared to the piecewise‐continuous 1‐D model. Estimated voltages on transmission lines oriented NW‐SE in southern Alberta are 10%–20% larger when using the MT impedances due to the polarized geoelectric field. As shown with forward modeling tests, the polarization is due to a feature in the lower crust (20–30 km depth) called the Southern Alberta British Columbia conductor that is associated with a Proterozoic tectonic suture zone. This forms an important link between ancient tectonic processes and modern‐day geoelectric hazards that cannot be modeled with a 1‐D analysis.